Regulation of the Nrf2/HO-1 pathway in chronic obstructive pulmonary disease-induced muscle atrophy using Jinshui Liujian decoction and Bajitian pills: insights from network pharmacology and animal models - Bai-Yang Lin; Li Bai; Sheng-Long Wang (Hereditas)
Abstract Objective This study aimed to investigate the therapeutic effects of the combination of modified Jinshui Liujian decoction and Bajitian pills (TCM) on chronic obstructive pulmonary disease (COPD)-induced muscle atrophy using network pharmacology and animal model experiments. Methods Network pharmacology technique has been employed to analyze the potential targets of TCM on treating COPD. In vivo, COPD mice model was induced by lipopolysaccharide (LPS) combined with smoke treatment. To comparing the protective effects of TCM on this disease, these parameters including general condition, serum inflammatory factors, protein expression levels, gene copies, and histopathological changes in the lungs and gastrocnemius muscle mass have been further assessed in mouse in different groups. Results Network pharmacology analysis identified 203 intersecting targets, primarily associated with apoptosis, phosphorylation, and inflammatory response. Animal experimental demonstrated that TCM could significantly improve the decreased skeletal muscle mass (p < 0.001), abnormal histopathologic morphology, decreased superoxide dismutase (SOD, p < 0.05), increased levels of serum malondialdehyde (MDA, p < 0.001) and tumor necrosis factor-α (TNF-α, p < 0.001) as compared to model group. Further mechanism exploration showed that a significant increase on the gene and proteins levels of nuclear factor erythroid 2-related factor 2 (NRF2, p < 0.05) and heme oxygenase-1 (HO-1, p < 0.05) have been observed in TCM-treated animals compared with that of in model animals. Interestingly, some indicators (serum MDA/SOD/TNF-α, RNA and protein levels of NRF2 and HO-1) showed more positive changes in TCM combined with western medicine (TCM-WN) - treated animals compared with that of TCM-treated animals. Conclusion Modified Jinshui Liujian decoction and Bajitian pills effectively mitigate muscle atrophy associated with COPD by modulating the Nrf2/HO-1 pathway through multi-target mechanisms. The combined TCM and WM therapy demonstrates enhanced therapeutic efficacy compared to monotherapy.